Removal and prediction of chemicals in anaerobic–anoxic–aerobic wastewater treatment system: Case study on organophosphates - Linjun Zhou; Xinfeng Yang; Wen Gu; Jie Gu; Weilong Xing; Lei Wang; Lili Shi; Jing Liang; Tianyun Wang (Emerging Contaminants)
Distribution and removal of chemicals in wastewater treatment plants (WWTPs) have mainly relied on mathematical models. Existing exposure assessment models such as SimpleTreat, STPWIN are based on conventional activated sludge processes. There is an urgent need to develop an A2/O-based WWTPs exposure assessment model. Organophosphates (OPEs) have different physical and chemical properties and potential environmental risks. The fate and biodegradation kinetics of three types of OPEs, including alkyl OPEs, chlorinated OPEs and triphenyl ester OPEs, were studied in a laboratory-scale anaerobic/anoxic/aerobic (A2/O) sewage treatment system and batch reactors. The three types of OPEs had different anaerobic, anoxic, and aerobic removal characteristics. A compensation mechanism was found between anaerobic and anoxic/aerobic removal. When the hydraulic retention time decreased from 82 to 20.5 h, the removal efficiencies in the anaerobic unit decreased, while those in the anoxic unit increased; as a result, the total removal efficiencies remained high (>80 %) for all OPEs except triphenyl phosphate (65.5%–75.1 %). The concept of effective sludge concentration (MLSSeff) was proposed to illustrate the compensation mechanism and calibrate the second-order kinetic equation for predicting pollutant removal in the A2/O system: MLSSeff = ken × MLSS, where ken is a constant related to the influent total organic carbon content (TOC). The influent TOC contents of the anoxic and aerobic units affected the value of MLSSeff and OPEs removal. The results are of great significance for assessing OPEs exposure and predicting exposure to emerging micropollutants in sewage treatment systems.